Lessons from pathological analysis of recurrent early esophageal squamous cell neoplasia after complete endoscopic radiofrequency ablation - Wang, Wen-Lun; Chang, I-Wei; Chen, Chien-Chuan; Chang, Chi-Yang; Tseng, Cheng-Hao; Tai, Chi-Ming; Lin, Jaw-Town; Wang, Hsiu-Po; Lee, Ching-Tai (Endoscopy, 2018)
Background Endoscopic radiofrequency ablation (RFA) is a treatment option for early esophageal squamous cell neoplasia (ESCN); however, long-term follow-up studies are lacking. The risks of local recurrence and “buried cancer” are also uncertain.Methods Patients with flat-type ESCN who were treated with balloon-type ± focal-type RFA were consecutively enrolled. Follow-up endoscopy was performed at 1, 3, and 6 months, and then every 6 months thereafter. Endoscopic resection was performed for persistent and recurrent ESCN, and the histopathology of resected specimens was assessed. Results A total of 35 patients were treated with RFA, of whom 30 (86 %) achieved a complete response, three were lost to follow-up, and five (14 %) developed post-RFA stenosis. Two patients had persistent ESCN and received further endoscopic resection, in which the resected specimens all revealed superficial submucosal invasive cancer. Six of the 30 patients with successful RFA (20 %) developed a total of seven episodes of local recurrence (mean size 1.4 cm) during the follow-up period (mean 40.1 months), all of which were successfully resected endoscopically without adverse events. Histological analysis of the resected specimens revealed that six (86 %) had esophageal glandular ductal involvement, all of which extended deeper than the muscularis mucosae layer. Immunohistochemistry staining for P53 and Ki67 suggested a clonal relationship between the ductal involvement and epithelial cells. None of the tumors extended out of the ductal structure; no cases of cancer buried beneath the normal neosquamous epithelium were found.Conclusions Because ductal involvement is not uncommon and may be related to recurrence, the use of RFA should be conservative and may not be the preferred primary treatment for early ESCN.